High Fas ligand expression on lymphocytes in lesions of ulcerative colitis. Issue 1 (1st July 1998) - Ueyama, H; Kiyohara, T; Sawada, N; Isozaki, K; Kitamura, S; Kondo, S; Miyagawa, J; Kanayama, S; Shinomura, Y; Ishikawa, H; Ohtani, T; Nezu, R; et al.
Abstract : Background —The pathogenesis of ulcerative colitis is unclear, but cytotoxic T lymphocytes infiltrating the mucosa have been implicated in mucosal damage. The Fas ligand (FasL), expressed on cytotoxic T lymphocytes, induces apoptosis in cells expressing Fas. Aim —To analyse FasL expression in affected colonic mucosa to ascertain Fas-FasL interaction in ulcerative colitis. Methods —FasL mRNA was quantified in colonic mucosal specimens from healthy subjects and patients with ulcerative colitis or Crohn's disease, using the competitive reverse transcription polymerase chain reaction. FasL mRNA localisation was determined by in situ hybridisation. Expression of Fas in colonic mucosa was analysed immunohistochemically. Phenotypes of lamina propria lymphocytes that expressed FasL were analysed by flow cytometry. Results —FasL mRNA was strongly expressed in active ulcerative colitis lesions, but not in those associated with active Crohn's disease or active proctitis-type ulcerative colitis. In situ hybridisation showed that FasL mRNA expression occurred in mononuclear cells infiltrating lesions. Fas was expressed in epithelial cells in ulcerative colitis and Crohn's disease, and in normal subjects. Cytometry showed that FasL was expressed in CD3 lymphocytes infiltrating the lamina propria in active lesions. Conclusions —FasL is expressed in CD3 lymphocytes infiltrating into ulcerative colitis but not Crohn's disease lesions, suggesting that Fas-FasL induced apoptosis participates in the mucosal damage of ulcerative colitis.